2020
DOI: 10.1159/000509038
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Oxidative Stress, Intermittent Hypoxemia, and Hospital Duration in Moderate Preterm Infants

Abstract: <b><i>Introduction:</i></b> Lipid peroxidation products are present following oxidation of polyunsaturated fatty acids in the eye, brain, and various cell membranes. Elevated levels of lipid peroxidation products and increased intermittent hypoxemia (IH) events have been associated with adverse outcomes in extremely preterm infants. The moderate preterm newborn has a still-developing oxidant defense system and immature respiratory control, but little is known about lipid peroxidation le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The same group studied the role of various biochemical markers of oxidative stress in moderate preterm infants and their role in the prolongation of hospitalisation. The authors reported that at 7 days of life, Isofurans, products of lipid peroxidation with a substituted tetrahydrofuran ring were significantly correlated with an increased length of hospitalisation 24 . A study by Kuligowski et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The same group studied the role of various biochemical markers of oxidative stress in moderate preterm infants and their role in the prolongation of hospitalisation. The authors reported that at 7 days of life, Isofurans, products of lipid peroxidation with a substituted tetrahydrofuran ring were significantly correlated with an increased length of hospitalisation 24 . A study by Kuligowski et al .…”
Section: Discussionmentioning
confidence: 98%
“…The authors reported that at 7 days of life, Isofurans, products of lipid peroxidation with a substituted tetrahydrofuran ring were significantly correlated with an increased length of hospitalisation. 24 A study by Kuligowski et al found that infants with higher urinary elimination of isoprostanes and isofurans in the first week of life had a higher risk of developing bronchopulmonary dysplasia later on. 25 A separate review by Torres-Cuevas I reported a correlation between the amount of oxygen received and level of biomarkers of oxidative stress and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, oxidative stress could be a mechanism linking IH events and downstream morbidities, leading to prolonged hospitalization [22][23][24][25]. Preliminary data in moderately preterm infants (31 to <34 weeks' gestation), who exhibit a low incidence of IH events, have shown a relationship between increased IH frequency and elevated urine lipid peroxidation by-products of docosahexaenoic acid and adrenic acid, which in turn were associated with the length of stay [8]. Inflammation may be another mechanism by which IH could lead to the need for prolonged hospitalization, such as through the development of BPD [25].…”
Section: Discussionmentioning
confidence: 99%
“…Some maternal and neonatal factors, such as maternal hypertension, lower birth weight, infant sex, sepsis, and other clinical markers of severity of illness, have been associated with prolonged length of stay [2][3][4][5][6]. Emerging data indicate physiological instability manifesting as intermittent hypoxemia (IH) may also be associated with length of stay [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The same group studied the role of various biochemical markers of oxidative stress in moderate preterm infants and their role in the prolongation of hospitalization. The authors reported that at 7 days of life, Isofurans, products of lipid peroxidation with a substituted tetrahydrofuran ring, and not Isoprostane was signi cantly correlated with increased length of hospitalization (33).…”
Section: Discussionmentioning
confidence: 99%